Optimization of SnO2 electron transport layer for efficient planar perovskite solar cells with very low hysteresis. Issue 1 (13th November 2021) - Eliwi, Abed Alrhman; Malekshahi Byranvand, Mahdi; Fassl, Paul; Khan, Motiur Rahman; Hossain, Ihteaz Muhaimeen; Frericks, Markus; Ternes, Simon; Abzieher, Tobias; Schwenzer, Jonas A.; Mayer, Thomas; Hofmann, Jan P.; Richards, Bryce S.; et al.
Abstract : In this work, we introduce a bilayer ETL composed of lithium (Li)-doped compact SnO2 (c-SnO2 ) and potassium-capped SnO2 nanoparticle layers (NP-SnO2 ) to enhance the electron extraction and charge transport properties in perovskite solar cells, resulting in an improved PCE and a strongly reduced J – V hysteresis. Abstract : Nanostructured tin oxide (SnO2 ) is a very promising electron transport layer (ETL) for perovskite solar cells (PSCs) that allows low-temperature processing in the planar n–i–p architecture. However, minimizing current–voltage ( J – V ) hysteresis and optimizing charge extraction for PSCs in this architecture remains a challenge. In response to this, we study and optimize different types of single- and bilayer SnO2 ETLs. Detailed characterization of the optoelectronic properties reveals that a bilayer ETL composed of lithium (Li)-doped compact SnO2 (c(Li)-SnO2 ) at the bottom and potassium-capped SnO2 nanoparticle layers (NP-SnO2 ) at the top enhances the electron extraction and charge transport properties of PSCs and reduces the degree of ion migration. This results in an improved PCE and a strongly reduced J – V hysteresis for PSCs with a bilayer c(Li)-NP-SnO2 ETL as compared to reference PSCs with a single-layer or undoped bilayer ETL. The champion PSC with c(Li)-NP-SnO2 ETL shows a high stabilized PCE of up to 18.5% compared to 15.7%, 12.5% and 16.3% for PSCs with c-SnO2, c(Li)-SnO2 and c-NP-SnO2 as ETL, respectively.